The Paradox of Knowledge and Practice: Nutritional Status and Diet Quality Among Indonesian Food and Nutrition Science Students - Ratih Paramastuti; Yasmin Aulia Rachma; Rafli Zulfa Kamil (Diponegoro University, 2025)
Nutritional status and dietary adequacy are fundamental to health and well-being, particularly among university students who often struggle to maintain balanced diets due to academic pressures and lifestyle constraints. Paradoxically, students enrolled in food and nutrition science programs, despite their academic exposure, may still exhibit suboptimal dietary behaviours. This study aimed to evaluate Indonesian undergraduate students' nutritional status and macronutrient adequacy in food and nutrition science. A descriptive cross-sectional survey was conducted involving 130 participants. Anthropometric measurements were collected to calculate Body Mass Index (BMI), and dietary intake was assessed using self-reported food records. Nutrient intakes were analyzed and compared against individual estimated requirements to determine adequacy. The BMI data showed that 17% of students were underweight, 45% had a normal weight, and 38% were overweight or obese. Mean energy intake (1287.66 ± 429.38 kcal) was substantially below the estimated requirement (1830 ± 323 kcal), with only 72.07% adequacy. Carbohydrate intake was critically low, meeting just 53.90% of the requirement, with 86% of students consuming inadequate amounts. Protein intake reached moderate adequacy (81.36%), while fat intake exceeded recommended levels in over half of the respondents (110.87% adequacy). Furthermore, 65% of students had inadequate energy intake and 55% consumed excess fat. These findings reveal the coexistence of undernutrition and overnutrition, reflecting a double burden of malnutrition in a population expected to possess greater nutritional awareness. The disconnect between knowledge and practice underscores the urgent need for strengthened nutrition education and campus-based interventions to foster healthier dietary habits and mitigate long-term health risks.